Pengembangan Sensor Kimia Berbasis Kertas Untuk Penetapan Kadar Kafein Sampel Kopi - Mochammad Amrun Hidayat; Noviani Tri Wahyuning; Indah Yulia Ningsih; Bambang Kuswandi (Universitas Andalas, 2023)
The caffeine chemical sensor was developed by co-immobilizing sodium periodate (NaIO4), 3-methyl-2-benzothiazolinone hydrazone (MBTH), and acetic acid (CH3COOH) onto paper by using an adsorption technique. The addition of caffeine solution could change the color of the sensor from white to pale blue which can be then captured by using a flatbed scanner and quantified by the ImageJ program, known as a scanometric technique. Method validation such as linearity, LOD, LOQ, precision, and accuracy of the sensor was done by using caffeine standards. The result of caffeine analysis using the developed chemical sensor-scanometric method agreed with that of the spectrophotometric method, suggesting that the developed sensor with scanometric technique can be used as an alternative method for caffeine assay in coffee samples.